Travel cost adjustment of international multiple destination visitors to the Kilim Karst Geoforest Park, Langkawi, Malaysia - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (IDOSI Publications, 2015)
Kilim Karst Geoforest Park (KKGP) located in Langkawi island offers pristine nature-based attractions to visitors. Apart from local visitors, the park receives many international visitor arrivals from all over the world. The demand model of international visitors to the park can be developed using one of the common environmental valuation techniques, the Travel Cost Method (TCM). And, using the demand curve, the benefit obtained by the international visitors to the park can be estimated using the concept of consumer surplus. In this research, the Individual Travel Cost Model (ITCM) has been employed. One of the common issues in travel cost studies is to obtain the specific travel cost attributable to the specific location for multiple destination visitors. Thus, the article determines the consumer surplus value of international visitors from the travel cost adjustment. A structured questionnaire and face-to-face data collection method were employed to obtain the primary data from 330 international visitors using the purposive sampling technique. The study has found that the consumer surplus estimated using the unadjusted travel cost model was greater than for the adjusted travel cost model thus suggesting an overestimation of the benefit gained by visitors. The consumer surplus value was estimated to be ϵ 216/ RM 864.